THE POLICY OF CRIMINAL LAW FORMULATION CONCERNING ERADICATION OF RELIGIOUS OFFENSE IN ORDER OF CRIMINAL LAW REFORMATION - Amin, Idi (Jurnal IUS (Kajian Hukum dan Keadilan), 2014)
Indonesia is the country that believes in God and having a philosophy of divinity, therefore, thetranquility of religious life is of a legal matter as well as public interest that should be protected.Therefore , since the legal protection on the legal matter is for all citizens, the stipulation of religionoffense must be regulated and protected within criminal law. Based on the above consideration there are several problems to be formulated. These are what is the formulation policy of the available criminal law in overcoming the religious offense. And, how the formulation policy of criminal law in the future in overcoming of religious offense in terms of the renewal of criminal law in Indonesia ?. This research is an analytical descriptive research with normative juridical approach. The data is a secondary data derived from primary, secondary, and tertiary law materials that are obtained through bibliography and documentary studies from secondary data that have been analyzed. The research concluded that a criminal law that is currently used to overcome religious offense is Criminal Code (KUHP) but still with several weaknesses that this offense is considered as the crime over public interest. There is disharmony between status and explanation of offense by either text or formulation. The religious offense within Criminal Code concept 2005 is formulated as Criminal Act for religion and relating to either religion or religious life. The formulation of criminal law in the future should consider the integrating of religion offense in Criminal Code concept 2005 by considering several things as follows: 1). harmonization of criminal act matter, 2). formulation policy of criminal responsibility, and 3) formulation policy of criminal and criminalizing systems.Keywords : Formulation Policy, Religion Offense, and Law Renewal